Why Community Health Systems Have Not Flourished in High Income Countries: What the Australian Experience Tells Us - Fran Baum; Toby Freeman (Kerman University of Medical Sciences, 2022)
Background  Despite the value of community health systems, they have not flourished in high income countries and there are no system-wide examples in high income countries where community health is regarded as the mainstream model. Those that do exist in Australia, Canada, the United States and the United Kingdom provide examples of comprehensive primary healthcare (PHC) but are marginal to bio-medical primary medical care. The aim of this paper is to examine the factors that account for the absence of strong community health systems in high income countries, using Australia as an example.Methods  Data are drawn from two Australian PHC studies led by the authors. One examined seven case studies of community health services over a five-year period which saw considerable health system change. The second examined regional PHC organisations. We conducted new analysis using the 'three I's' framework (interests, institutions, ideas) to examine why community health systems have not flourished in high-income countries.Results  The elements of the community health services that provide insights on how they could become the basis of an effective community health system are: a focus on equity and accessibility, effective community participation/control; multidisciplinary teamwork; and strategies from care to health promotion. Key barriers identified were: when general practitioners (GPs) were seen to lead rather than be part of a team; funding models that encourage curative services rather than disease prevention and health promotion; and professional and medical dominance so that community voices are drowned out.Conclusion  Our study of the community health system in Australia indicates that instituting such a system in high income countries will require systematic ideological, political and institutional change to shift the overarching government policy environment, and health sector policies and practices towards a social model of health which allows community control, and multidisciplinary service provision.